2009 International Conference on Information Management and Engineering 2009
DOI: 10.1109/icime.2009.106
|View full text |Cite
|
Sign up to set email alerts
|

Graph Coloring Problem Based on Learning Automata

Abstract: Abstract-The vertex coloring problem is a well-known classical problem in graph theory in which a color is assigned to each vertex of the graph such that no two adjacent vertices have the same color. The minimum vertex coloring problem is known to be an NP-hard problem in an arbitrary graph, and a host of approximation solutions are available. In this paper, four learning automata-based approximation algorithms are proposed for solving the minimum (vertex) coloring problem. It is shown that by a proper choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In Akbari Torkestani and Meybodi (in press-a, in press-b, in press-d, 2010), a group of variable action-set learning automata is used to solve the vertex coloring problem, or in Akbari Torkestani and Meybodi (in press-a, in press-b, in press-d, 2010) variable action-set learning automata cooperate to find the virtual backbone of the ad hoc networks. It has been shown in Thathachar and Harita (1987), Akbari Meybodi (2009a and2009b) that a learning automaton with a changing number of actions is absolutely expedient and also e-optimal, when the reinforcement scheme is L RÀ I . Such an automaton has a finite set of n actions, a={a 1 , a 2 , y a n }.…”
Section: Variable Action-set Learning Automatamentioning
confidence: 97%
See 1 more Smart Citation
“…In Akbari Torkestani and Meybodi (in press-a, in press-b, in press-d, 2010), a group of variable action-set learning automata is used to solve the vertex coloring problem, or in Akbari Torkestani and Meybodi (in press-a, in press-b, in press-d, 2010) variable action-set learning automata cooperate to find the virtual backbone of the ad hoc networks. It has been shown in Thathachar and Harita (1987), Akbari Meybodi (2009a and2009b) that a learning automaton with a changing number of actions is absolutely expedient and also e-optimal, when the reinforcement scheme is L RÀ I . Such an automaton has a finite set of n actions, a={a 1 , a 2 , y a n }.…”
Section: Variable Action-set Learning Automatamentioning
confidence: 97%
“…Such a code assignment problem is similar to the NP-hard vertex coloring problem in which no two neighboring clusters (or node) have the same code (or color). The code assignment algorithm we propose in this paper is a distributed version of the first learning automata-based graph coloring algorithm proposed in Akbari Meybodi (2009a and2009b). LACAA is a fully localized algorithm in which each cluster-head is assigned an interference-free code based only on the local (code assignment) information received from the cluster-head of its neighboring clusters.…”
Section: Learning Automata-based Code Assignment Algorithm (Lacaa)mentioning
confidence: 99%
“…We show this suitability by S(E). In [33], four learning automata-based approximation algorithms are proposed for solving the minimum (vertex) coloring problem.It is shown that by a proper choice of the parameters of the algorithm, the probability of approximating the optimal solution is as close to unity as possible.…”
Section: Prior Workmentioning
confidence: 99%
“…The last proposed algorithm is compared with CHECKCOL [13], GLS [9], ILS [5], TPA [6], AMACOL [1], some well-known coloring algorithms and the results show the efficiency of the algorithm [33] in terms of the color set size and running time of algorithm.Graph coloring problem is widely used in real life applications like computer register allocation, air traffic flow management, timetabling, scheduling, frequency assignment, and light wavelengths assignment inoptical networks. The approximation approaches reported in the literatures can be classified as local search approaches, genetic algorithms, fuzzy-based optimizations, evolutionary algorithms, simulated annealing methods, ant colony-based approaches, Markov chain approaches, and neural network approaches.…”
Section: Prior Workmentioning
confidence: 99%
“…Second, supporting the inter-cluster connections by assigning a code to each cluster (code assignment) so that no two neighboring or hidden clusters have the same code, and third, using an efficient TDMA scheme for channel access scheduling within each cluster. Code assignment problem is very similar to the NP-hard [27] vertex coloring problem [28] in graph theory. Besides the above mentioned TDMA schemes, we compare our proposed model with the TDMA part of the following CDMA/TDMA schemes.…”
mentioning
confidence: 99%